System on-chip implementation of genetic algorithm for problem solving - Yeo, Pen Meng. (2008)
This thesis describes a system on chip inplementation of Genetic Algorithm (GA) for problem solving. It studies the practicality and effect of integrating an entire system of problem-solving, which is typically implemented on a software platform, onto a single hardware chip.